Analisis Potensi Bahaya Keselamatan dan Kesehatan Kerja (K3) Pada Nelayan di Pesisir Pantai - Ershanda, Mayumi; Laili, Hasanatun; Ananda, Zahra; Hasibuan, Abdurrozzaq (PT. Alahyan Publisher Sukabumi, 2024)
Coastal work areas are also undeniably at great risk of occupational accidents. However, fishermen usually do not equip and use personal protective equipment and safety equipment. This makes the work of fishermen quite risky. The purpose of this study was to analyze the potential hazards of occupational safety and health in fishermen on the coast. This research is a literature review with data collection methods and uses literature studies. A literature study is conducted by searching for data from published articles or national journals related to the keywords of this research to be analyzed by accessing the database on Google Scholar, then the data is filtered again based on the title, abstract, and content that is in accordance with the research. The criteria for the selected articles are published 2020-2024, indexed by Google Scholar, indexed nationally and internationally, and indexed by students. The results of this literature study are potential occupational health and safety hazards in fishermen, namely chemical, physical, ergonomic, and psychosocial hazards. Translated with DeepL.com (free version).